Need for Cognition as a Mediating Variable Between Aggressive Communication Traits and Tolerance for Disagreement. Issue 4 (1st October 2016) - Linvill, Darren L.; Mazer, Joseph P.; Boatwright, Brandon C.
Abstract : This study examined the need for cognition as a mediator between aggressive communication traits and tolerance for disagreement. Previous research suggests that argumentativeness is a positive predictor of tolerance for disagreement, while verbal aggressiveness is a negative predictor of tolerance for disagreement. Our findings indicate that need for cognition positively mediates the relationship between argumentativeness and tolerance for disagreement, as well as verbal aggressiveness and tolerance for disagreement.